(untitled) (European Journal of Pure and Applied Mathematics, 2021)
In this article, we would like to state generalized results related to well-known Hermite− Hadamard dual inequality for p−convex functions using the newly introduced notion of (s, r)−convexity (s−convex function in mixed kind) with different techniques. Hence various established and new results would be captured as special case.